Gonioscopy-assisted Transluminal Trabeculotomy (GATT) combined phacoemulsification surgery: Outcomes at a 2-year follow-up - Wan, Yue; Cao, Kai; Wang, Jin; Sun, Yunxiao; Du, Rong; Wang, Ziyi; Zhang, Jidi; Wang, Huaizhou; Wang, Ningli (Eye (London), 2023)
Background/Objectives This study aimed to provide a 24-month follow-up on the surgical success and safety of gonioscopy-assisted transluminal trabeculotomy (GATT) combined with phacoemulsification and intraocular lens (IOL) implantation in the treatment of patients with primary open-angle glaucoma (POAG) combined cataract. Subjects/Methods We included 124 consecutive cases of POAG with microcatheter-assisted GATT or GATT combined with phacoemulsification and IOL implantation at Beijing Tongren Eye Centre between October 2019 and November 2020. Main outcome measures included surgical success rate, changes in IOP, number of antiglaucoma medications, best corrected visual acuity (BCVA), postoperative complications at baseline, and follow-up period of up to 24 months. Results In total, 58 eyes received GATT combined with phacoemulsification surgery and 66 eyes received GATT alone. The overall qualified success rate was 86.21% for eyes with GATT combined with phacoemulsification surgery, and 83.48% for eyes with GATT only at 24 months. IOP was reduced from 26.40 ± 6.37 mmHg on 3.12 ± 0.80 medications preoperatively to 14.61 ± 2.28 mmHg on 0.27 ± 0.71 medications at 12 months and 16.08 ± 2.38 mmHg on 0.45 ± 0.96 medications at 24 months after combined surgery. Additionally, mean BCVA improved from 0.75 ± 0.43 logMAR units preoperatively to 0.22 ± 0.18 logMAR units 24 months after combined surgery. No vision-threatening complications occurred during the 24-month follow-up. Conclusions The 24-month follow-up results of our study suggest that GATT combined with cataract surgery is a safe and effective treatment for decreasing IOP and number of medications in patients with POAG combined cataract.